Multiple Source Translation Micro-CT Improves Both Field-of-View and Spatial Resolution - Yu, Haijun; Ni, Song; Thies, Mareike; Wagner, Fabian; Huang, Yixing; Liu, Fenglin; Maier, Andreas (IEEE Transactions on Instrumentation and Measurement, 2024)
Object rotation is a classical data acquisition mode in micro-computed tomography (micro-CT) to capture radiographs from different angles for high-resolution three-dimensional reconstruction. However, this mode encounters two primary limitations: firstly, an undesired tradeoff arises between the field-of-view (FOV) and the spatial resolution; secondly, the spatial resolution is compromised due to insufficient radial sampling in the frequency domain. In this paper, we present a novel acquisition paradigm called multiple Source Translations micro-CT (mSTCT) to simultaneously improve FOV and spatial resolution. In mSTCT, the FOV is enlarged by extending the source translation distance and the spatial resolution is enhanced by refining the source sample spacing to increase the radial sampling in the frequency domain. Theoretically, mSTCT can enhance the FOV and spatial resolution to their physical limits. We formulate a central slice theorem for mSTCT to elucidate its fundamental principle. Subsequently, we derive a corresponding analytical algorithm without projection rebinning or stitching for reconstruction. The physical experiments conducted in this work validate the efficacy of mSTCT in terms of FOV extension and spatial resolution enhancement. As mSTCT is trivial to implement, it holds considerable promise for diverse scenarios demanding high-resolution and large FOV in Non-Destructive Testing (NDT) applications.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Data sampling; field-of-view (FOV); micro-computed tomography (micro-CT); scanning mode; spatial resolution.